The state of the art in treating patients with a dual diagnosis of chronic migraine and medication-overuse headache - Jevoux, Carla; Krymchantowski, Abouch; Silva-Néto, Raimundo Pereira; Krymchantowski, Ana Gabriela; Cotrik, Ervin Michelstaedter (Headache Medicine, 2023)
Migraine is a common, highly prevalent genetic neurological disorder. Its most burdensome form is the chronic migraine, which is clinically defined by the presence of headache on ≥15 days/month for longer than three months, with eight or more typical migraine days. Medication-overuse headache (MOH) is a secondary headache disorder associated with the overuse of symptomatic headache medications on ≥10 days/month for longer than 3 months. Chronic migraine and medication-overuse headache often coexist and most chronic migraineurs have medication overuse headache. Despite that, general practitioners and health professionals do not know about MOH. This review aims at presenting insights, recent knowledge, and guidance regarding the approach and treatments for patients with a dual diagnosis of chronic migraine and medication-overuse headache.